A Feminist Review of Behavioral Economic Research on Gender Differences. Issue 2 (3rd April 2019) - Sent, Esther-Mirjam; van Staveren, Irene
ABSTRACT: This study provides a critical review of the behavioral economics literature on gender differences using key feminist concepts, including roles, stereotypes, identities, beliefs, context factors, and the interaction of men's and women's behaviors in mixed-gender settings. It assesses both statistical significance and economic significance of the reported behavioral differences. The analysis focuses on agentic behavioral attitudes (risk appetite and overconfidence; often stereotyped as masculine) and communal behavioral attitudes (altruism and trust; commonly stereotyped as feminine). The study shows that the empirical results of size effects are mixed and that in addition to gender differences, large intra-gender differences (differences among men and differences among women) exist. The paper finds that few studies report statistically significant as well as sizeable differences – often, but not always, with gender differences in the expected direction. Many studies have not sufficiently taken account of various social, cultural, and ideological drivers behind gender differences in behavior.